2024
DOI: 10.1038/s41398-024-02852-9
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning and the prediction of suicide in psychiatric populations: a systematic review

Alessandro Pigoni,
Giuseppe Delvecchio,
Nunzio Turtulici
et al.

Abstract: Machine learning (ML) has emerged as a promising tool to enhance suicidal prediction. However, as many large-sample studies mixed psychiatric and non-psychiatric populations, a formal psychiatric diagnosis emerged as a strong predictor of suicidal risk, overshadowing more subtle risk factors specific to distinct populations. To overcome this limitation, we conducted a systematic review of ML studies evaluating suicidal behaviors exclusively in psychiatric clinical populations. A systematic literature search wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…These algorithms can be trained to classify and forecast future suicide attempts by utilizing data from diverse sources and integrating a wide array of clinical, neurobiological, behavioral, and social risk factors. In a recent systematic review [10], 81 studies using ML techniques to assess suicide risk or predict suicide attempts in individuals with mental disorders were examined. Despite methodological differences, most studies reported accuracies of 0.7 or higher, considering factors like previous attempts, disorder severity, and pharmacological treatments; however, only 3 of these studies tested their prediction on independent datasets.…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms can be trained to classify and forecast future suicide attempts by utilizing data from diverse sources and integrating a wide array of clinical, neurobiological, behavioral, and social risk factors. In a recent systematic review [10], 81 studies using ML techniques to assess suicide risk or predict suicide attempts in individuals with mental disorders were examined. Despite methodological differences, most studies reported accuracies of 0.7 or higher, considering factors like previous attempts, disorder severity, and pharmacological treatments; however, only 3 of these studies tested their prediction on independent datasets.…”
Section: Introductionmentioning
confidence: 99%